2022
DOI: 10.1021/acsnano.2c00378
|View full text |Cite
|
Sign up to set email alerts
|

Charge-Density-Wave Thin-Film Devices Printed with Chemically Exfoliated 1T-TaS2 Ink

Abstract: We report on the preparation of inks containing fillers derived from quasi-two-dimensional charge-density-wave materials, their application for inkjet printing, and the evaluation of their electronic properties in printed thin-film form. The inks were prepared by liquid-phase exfoliation of CVT-grown 1T-TaS2 crystals to produce fillers with nm-scale thickness and μm-scale lateral dimensions. Exfoliated 1T-TaS2 was dispersed in a mixture of isopropyl alcohol and ethylene glycol to allow fine-tuning of filler pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 59 publications
(103 reference statements)
0
8
0
Order By: Relevance
“…The charge-density-wave (CDW) phase is a macroscopic quantum state consisting of a periodic modulation of the electronic charge density accompanied by a periodic distortion of the atomic lattice. The early work on CDW effects, performed with bulk samples of the quasi-one-dimensional (1D) metallic crystals, revealed many spectacular phenomena: nonlinear electron transport, oscillating electric current for constant voltages, giant dielectric response, and multistable conducting states. Recent years witnessed a rebirth of the field of CDW materials and devices, partially driven by an interest in layered quasi-2D van der Waals materials where CDW phases can manifest themselves at room temperature (RT) and above. The size and geometry of quasi-2D CDW films provide compelling opportunities for device fabrication. The early studies of de-pinning of CDWs in quasi-2D materials reported certain common features among CDW phenomena in quasi-1D and quasi-2D systems. , However, there is also an understanding of differences in physics governing CDW phases in material systems of different dimensionalities and crystal structures. , …”
mentioning
confidence: 99%
“…The charge-density-wave (CDW) phase is a macroscopic quantum state consisting of a periodic modulation of the electronic charge density accompanied by a periodic distortion of the atomic lattice. The early work on CDW effects, performed with bulk samples of the quasi-one-dimensional (1D) metallic crystals, revealed many spectacular phenomena: nonlinear electron transport, oscillating electric current for constant voltages, giant dielectric response, and multistable conducting states. Recent years witnessed a rebirth of the field of CDW materials and devices, partially driven by an interest in layered quasi-2D van der Waals materials where CDW phases can manifest themselves at room temperature (RT) and above. The size and geometry of quasi-2D CDW films provide compelling opportunities for device fabrication. The early studies of de-pinning of CDWs in quasi-2D materials reported certain common features among CDW phenomena in quasi-1D and quasi-2D systems. , However, there is also an understanding of differences in physics governing CDW phases in material systems of different dimensionalities and crystal structures. , …”
mentioning
confidence: 99%
“…Exfoliated 1T‐TaS 2 and other CDW van der Waals fillers can be produced via the scalable and cost‐effective LPE technique. [ 72 ] It is already being used for the processing of graphene fillers for thermal interface materials. [ 73 ] It is worth noting that 1T‐TaS 2 preserves its unique CDW properties even in powder form.…”
Section: Resultsmentioning
confidence: 99%
“…The ordering of charge density wave (CDW) patterns in layered materials such as 1T-TaS 2 has been investigated for decades owing to its intriguing electronic state change accompanied by the structural phase transition, [1][2][3] and the promising applications in nanodevices such as field-effect transistors, [4] voltage oscillators, [5] ultrafast switches, [6,7] nonlinear thermal devices, [8] and ultrabroad band photosensitivity detector. [9] The CDW DOI: 10.1002/smll.202305159 pattern can become incommensurate or rearrange with phase slip under various stimuli such as temperature change, [10,11] pressure application, [12] doping, [13] and current or voltage pulse. [14,15] Besides, the spatial confinement of the CDW array has been investigated.…”
Section: Introductionmentioning
confidence: 99%